1998
DOI: 10.1021/ma9709664
|View full text |Cite
|
Sign up to set email alerts
|

Rigid-Rod Polyamides and Polyimides Derived from 4,3‘‘-Diamino-2‘,6‘-diphenyl- or Di(4-biphenylyl)-p-terphenyl and 4-Amino-4‘‘-carboxy-2‘,6‘-diphenyl-p-terphenyl

Abstract: 4,3‘‘-Diamino-2‘,6‘-diphenyl- or di(4-biphenylyl)-p-terphenyl (3a or 3b) and 4-amino-4‘‘-carboxy-2‘,6‘-diphenyl-p-terphenyl (6) were synthesized through pyrylium salts and used for the preparation of rigid-rod polyamides and polyimides. The polymers were characterized by inherent viscosity, elemental analysis, FT-IR, 1H-NMR, 13C-NMR, UV−vis, X-ray, differential scanning calorimetry (DSC), thermomechanical analysis (TMA), thermal gravimetric analysis (TGA) isothermal gravimetric analysis, and moisture absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…In order to meet these requirements, structural modifications of these polymers often become essential. Therefore, considerable efforts have been made in recent years to develop highly optical transparent, low dielectric constant, and low refractive index aromatic polyimides with good processability by the incorporation of flexible linkages, [4,5] bulky pendant groups [6][7][8], and noncoplanar biphenylene moieties [9,10] into the polymer backbones. It has been observed that introduction of fluorinated substituents can impart many of these desirable properties to the polymers, making them suitable for a much wider range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet these requirements, structural modifications of these polymers often become essential. Therefore, considerable efforts have been made in recent years to develop highly optical transparent, low dielectric constant, and low refractive index aromatic polyimides with good processability by the incorporation of flexible linkages, [4,5] bulky pendant groups [6][7][8], and noncoplanar biphenylene moieties [9,10] into the polymer backbones. It has been observed that introduction of fluorinated substituents can impart many of these desirable properties to the polymers, making them suitable for a much wider range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly mentioned aromatic and semiaromatic polyamides can not be processed by melting method due to their high melting temperature and relatively lower decomposition temperatures [4][5][6]. Therefore, several approaches have been made through synthetic modification by the incorporation of flexible linkages [7,8], bulky pendant groups [9] and noncoplanar biphenylene moieties [10] into the polymer backbones. Poly(nonamethylene terephthalamide) (PA9T) inherits the merits of the heat resistance of aromatic polyamides and the processing ability of aliphatic polyamides [11].…”
Section: Introductionmentioning
confidence: 99%
“…TGA traces reveal all cardo polyamides not to decompose around or below 450°C in nitrogen or air. Decomposition temperatures of 10% weight loss (Td 10 ) were from 468-523oC and 503-5530C in nitrogen and air, respectively. Td 10 of the polymers in air was higher than in nitrogen.…”
Section: Polymer Characterizationmentioning
confidence: 99%